From Innocence to Infection: Interpreting “The Sick Rose” in the Light of the COVID‐19 Crisis - A. S. ROSHEED, Mostafa; SAHAN, Wafa’ Abbas (Anafora, 2024)
This paper examines the enduring relevance of William Blake’s poem “The Sick Rose” in the context of contemporary challenges, particularly the COVID‐19 pandemic. Despite its pre‐pandemic origin, the poem’s themes of hidden vulnerabilities, obscured intentions, and transient beauty resonate profoundly with current complexities. Through comprehensive analysis of symbolism, the study highlights literature’s adaptability in reflecting evolving human experiences. Slavoj Žižek’s book Pandemic!: COVID‐19 Shakes the World offers a lens to understand these themes, as it explores hidden threats, shattered illusions, global chaos, gradual transformation, and human frailty caused by the pandemic. This analysis magnifies the poem’s resonance, demonstrating literature’s power to mirror shifting human narratives. Ultimately, the research underscores the unbreakable connection between art and life, presenting “The Sick Rose” as a testament to the enduring interplay between artistic expression and the evolving contours of existence.